Efforts to Improve The Ability of Self Efficacy Students with The AIR Learning Model - Sumliyah Sumliyah; Putik Rustika; Asep Lukman Firmansyah (EduMa: Mathematics education learning and teaching, 2020)
The process of observation and interview with one of the teachers of SMP Islamiyah Weru is the background of this research by producing information that found difficulties and self-efficacy of students in solving some of the problems given by the teacher. This study aims to improve the ability of self-efficacy in students. Quantitative method, the type of research uses a quasi-experiment and the design used is nonequivalent control group. Application of the Auditory learning model, Intellectually, Repetition (AIR) contributes to improving the ability of self-efficacy with the results obtained namely the difference in the increase in self-efficacy in students whose learning uses the AIR learning model with Expository learning models with the average N-Gain self-efficacy of classroom students Experiment is higher than the control class so it can be concluded that the increase in students' self-efficacy in the experimental class is better than in the control class